Marine macroalgae Pelvetia canaliculata (Phaeophyceae) as a natural cation exchanger for cadmium and lead ions separation in aqueous solutions - Fabíola V. Hackbarth (2014)
This work aims to add value to marine brown macro-algae Pelvetia canaliculata (Linnaeus) Decaisne and Thuret through its use as cation exchanger for separation and recovery of cadmium and lead ions in aqueous solution, as a cost effective and environmental friendly process. Raw algae was established as a cation exchanger, in which cadmium and lead ions present in the solution exchange with Na+, K+, Ca2+ and Mg2+, bound to the negatively functional groups existing on the algae surface, with a stoichiometric ratio of 1:1 between ions of the same charge and 2:1 between monovalent and divalent ions. Batch equilibrium and kinetic experiments were conducted at different pH values using Na-loaded algae. The main functional groups present on the surface of the algae responsible for binding metals, as determined by Fourier Transform Infrared (FTIR) analysis, are weakly acidic carboxylic groups and strongly acidic sulfonic groups. Considering the potentiometric titration and biomass esterification results, the amount of sulfonic and carboxylic groups is 1.0 mmol/g and 1.5 mmol/g, respectively, which is in agreement with the total amount of Na+ present at the surface of Na-loaded biomass (2.5 mEq/g) and total amount of light metals present at the surface of raw biomass (2.5 mEq/g). Maximum biosorption capacity of Pb2+ at pH 4.0 was 1.25 mmol/g (2.5 mEq/g; 259 mg/g) and for Cd2+ at pH 4.5 was 1.25 mmol/g (2.5 mEq/g; 140 mg/g). The mass action law for the ternary mixture was able to predict the equilibrium data, with the selectivity coefficients alpha(Cd)(Na) = 337 and alpha(Pb)(Na) = 941 for carboxylic and alpha(Cd)(Na) = 38 and alpha(Pb)(Na) = 1695 for sulfonic groups, revealing a higher affinity of the biomass towards lead ions. A mass transfer model, considering equilibrium given by the mass action law, and a linear driving force model for intraparticle diffusion, was able to fit well the batch kinetic data.